179 Improving Operative Notes in Upper GI Surgery: An Innovative QI Project Utilising Existing Electronic Hospital Systems. (4th May 2021) - Sadik, H; Butt, A; Gowie, Z; Carew, J; Mehta, A; Sheth, H
Abstract: Introduction: Operative notes play a valuable role in ensuring that surgical patients receive consistent and adequate care. There are many inherent difficulties affecting their quality. We performed a QI project to improve surgical operative notes at our centre. Method: A questionnaire assessing subjective quality of operative notes was sent to all foundation doctors delivering post-operative care. Compliance to each inclusion recommendation in the RCS guidelines was analysed. A standardised template for operative notes was incorporated into the hospital's electronic records system, compliance was then reassessed. Results: Questionnaire responses (16) were better for typed vs hand-written notes in all domains: ease of accessing notes, following intra-operative steps, following post-operative plans and frequency of asking for additional information regarding plans. After implementation of the template, mean compliance across 19 RCS parameters improved from 69% (55 operations) to 89% (46 operations). Number of parameters with 100% compliance improved from 2/19 to 8/19. Compliance increased in 14/19 parameters, there was no change in 2/19 (already 100%) and a reduction was seen in 3/19. Conclusions: Results from our analysis and questionnaire showed that typed notes were favourable when compared to hand-written. The introduction of a standardised electronic template, without investment in new software, improved compliance to RCS guidelines.